EMBEDDED AND AUTONOMOUS MARKETS IN NORTH KOREA'S FISHING INDUSTRY: RESOURCE SCARCITY, MONITORING COSTS, AND EVOLVING INSTITUTIONS. (March 2021) - Ward, Peter; Lankov, Andrei; Kim, Jiyoung
Abstract: North Korea today is a most unusual post-socialist state. Market actors and market prices are integral to economic life, but private property remains illegal, and private enterprise outside the household is de jure non-existent. In such an institutional context, some market processes are more autonomous in relation to the state, while others are more embedded within state structures. In this article, we offer a theoretical account of the shape that North Korea's market economy has taken, developed from a set of fishing industry case studies. We note four broad categories of enterprises: closely embedded, loosely embedded, semi-autonomous, and autonomous. By relative autonomy/embeddedness we mean control over fixed assets, cash flow, and operational decisions such as wage and price setting. We postulate three major determinants of embeddedness/autonomy: (1) relative strategic resource scarcity between state and market actors, (2) monitoring costs, and (3) institutional evolution that reflects these realities, though to varying extents.